Workplace coaching: a meta-analysis and recommendations for advancing the science of coaching - Cannon-Bowers, Janis A.; Bowers, Clint A.; Carlson, Catherine E.; Doherty, Shannon L.; Evans, Jocelyne; Hall, Julie (Frontiers in Psychology, 2023)
Workplace coaching has experienced a dramatic rise in popularity over the past decade and is one of the fastest growing performance-enhancing interventions used by modern organizations. Yet, despite its popularity, workplace coaching has not been the subject of much empirical research and a true science of coaching has yet to be developed. The purpose of this research was to update prior metaanalyses that investigated the impact of coaching on organizational outcomes and to provide recommendations for how the field needs to evolve. Results indicated that, consistent with prior meta-analyses, workplace coaching is effective in achieving positive organizational outcomes. The effects of several moderators were also investigated. Finally, we discuss the results in terms of recommendations for future directions that we believe will establish and advance the science of coaching.